Physical Growth and Echocardiographic Findings in Children with Down Syndrome - Sudigdo Sastroasmoro; Mathilda Y. lnkiriwang; Bambang Madiyono; lsmet N Oesman (Paediatrica Indonesiana, 1998)
We compared the physical growth, nutritional status, and echocardiographic findings in children aged 3-7 years with Down syndrome who had no congenital heart disease. Thirty such patients who consecutively referred to the Division of Cardiology, Department of Child Health, Medical School, University of Indonesia/Cipto Mangunkusumo Hospital, Jakarta, were compared with sex and age matched controls consisted of normal children attending the Department. It appears that growth and nutritional status of children with Down syndrome tended to be retarded when compared to those of the controls. However, no significant difference were found on the M-mode echocardiographic values of the left ventricle, except that the left ventricular posterior wall thickness in study subjects was more that that of the controls. We concluded that although the pulmonary architecture of patients with Down syndrome is thought to be less developed than that of normal children, it does not affect the left ventricular measurements and function as measured by M-mode echocardiography.